Study of the effect of drill bits hardness, drilling machine operating parameters and rock mechanical parameters on noise level in hard rock drilling process. (1st January 2021) - Piri, Mostafa; Mikaeil, Reza; Hashemolhosseini, Hamid; Baghbanan, Alireza; Ataei, Mohammad
Graphical abstract: Highlights: The noise level can be an indicator to evaluate the performance of drilling tools. By increasing the hardness of the drilling bits, the produced noise level is less. By increasing the rock mechanical parameters, the produced noise level is greater. Multivariate statistical models have good accuracy in predicting the noise level. Abstract: Rock drilling systems have extensive use in many industries including mining, construction, and oil and water extraction. The process of drilling inevitably creates some noise at the drill-rock collision surface. Loud noises cause serious safety issues in the workplace. Noise level can also be a good indicator of the performance of the drilling tool. This study measured and compared the noise levels created in the drilling environment during the drilling of three types of hard rock, namely Khoshtinat, white Natanz and Nehbandan granites with three types of drill bit with tungsten carbide, Diamond-DLC, and Titanium-Aluminum-Silicon coatings. The software SPSS was used to develop several multivariate linear and nonlinear statistical models for predicting noise level. The results showed that as the mechanical parameters of the drilled rock increased, so did the noise level. Also, in all specimens, as the hardness of the drill bit increased, the noise level generated by drilling decreased. The results of statistical tests showed, at above 90% confidence level, that the developed models can provide reasonably accurate predictions of the noise level to be generated in drilling environments based on the mechanical properties of the drilled rock, the hardness of the drill bit, and operating specifications.